An experimental and numerical investigation on dynamic mechanical behavior and fracture characteristics of sandstone under active confining pressures - Sheng-Qi Yang; Ye Li; Wen-Ling Tian; Bo-Wen Sun; Zhen Zhong; Xiao-Shuang Li (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract This study aims to investigate the dynamic mechanical properties and failure mechanisms of red sandstone under varying strain rates and confining pressures, using a modified confining pressure split Hopkinson pressure bar system, focus on investigating the mechanical behavior, stress–strain response, energy dissipation mechanisms, and ultimate failure modes of red sandstone specimens subjected to varying strain rates and confining pressures. The findings reveal that red sandstone exhibited significant plastic yielding, with strain rate effects enhancing its ductility and peak strain. As strain rate and confining pressure increased, parameters for instance elastic modulus, compressive strength, and strain rate strengthening also elevated. Confining pressure constrained deformation, resulting in a decrease in strain rate as confining pressure increased, while maintaining a constant impact velocity. Reflection energy exhibited a positive correlation with strain rate but remained unaffected by confining pressure, suggesting that it was solely influenced by the strain rate. Dissipated energy demonstrated a clear dependence on both confining pressure and strain rate, with an increase observed for both factors. Furthermore, a positive correlation was established between dissipated energy and dynamic compressive strength. Additionally, the failure mode of red sandstone was found to be predominantly shear failure, characterized by core-retaining cones and large fragments, with fragmentation following a fractal distribution law. The fractal dimension of the fragments ranged from 2.20 to 2.80 under active confining pressure.